2015
DOI: 10.1109/tnsre.2015.2425474
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Neuro-Motor Recovery From Stroke With High-Resolution EEG, Robotics and Virtual Reality: A Proof of Concept

Abstract: A novel system for the neuro-motor rehabilitation of upper limbs was validated in three sub-acute post-stroke patients. The system permits synchronized cortical and kinematic measures by integrating high-resolution EEG, passive robotic device and Virtual Reality. The brain functional re-organization was monitored in association with motor patterns replicating activities of daily living (ADL). Patients underwent 13 rehabilitation sessions. At sessions 1, 7 and 13, clinical tests were administered to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…In addition, it is possible to use EEG during task performance in an ecological environment. This framework allows exploration of the brain's functional changes and monitoring of brain activity in response to rehabilitation tasks [201][202][203], potentially shedding light on specific brain-behavior relationships.…”
Section: Neural and Muscular Correlates Of The Sensorimotor Performancementioning
confidence: 99%
“…In addition, it is possible to use EEG during task performance in an ecological environment. This framework allows exploration of the brain's functional changes and monitoring of brain activity in response to rehabilitation tasks [201][202][203], potentially shedding light on specific brain-behavior relationships.…”
Section: Neural and Muscular Correlates Of The Sensorimotor Performancementioning
confidence: 99%
“…It was found that neurophysiological data can be used to recognize the patterns of external stimuli (Speier et al, 2014; Bertrand, 2015; Comani et al, 2015). In this section, the CTL classifier is used to design an AA system that is able to realize adaptive function allocation between human operator and machine.…”
Section: Design and Simulation Of Adaptive Human-machine Systemmentioning
confidence: 99%
“…By collecting electroencephalography (EEG) signals from the scalp, Comani et al detected real-time cortical electrical activity and identified instant and synchronized changes in the cortex ( 17 ). To date, several studies have reported relationships between EEG features and spasticity.…”
Section: Introductionmentioning
confidence: 99%